Digital Hr : Digital Transformation In Increasing Productivity In The Work Environment - Ananda Roro Wulandari; Afninda Ainun Arvi; Mohammad Irfandi Iqbal; Fatrining Tyas; Indra Kurniawan; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Digitalization in human resource management (HRM) has become a vital element in the digital era, enabling companies to evolve in a modern way and gain a competitive edge. This research explores the benefits of digitalization, including enhanced operational efficiency, data-driven decision-making, and improved employee experiences. However, the study also identifies data security risks and workplace culture changes associated with digital transformation. HRM plays a crucial role in managing these changes by understanding the dynamics among generations of employees, fostering cross-generational communication, and utilizing technology wisely. Successful HRM strategies involve integrating new policies, preserving organizational values, and managing diversity. Effective HRM leadership entails policy formulation, communicating a vision for change, building strong relationships with employees, and efficient technology integration. Concrete steps include training to optimize technology usage, understanding the unique needs of different employee generations, and creating a work culture that supports digital transformation. By considering these aspects, organizations can navigate change with readiness, strengthen HRM performance, and adapt to the evolving dynamics of the working world.